Food consumption and adherence to dietary guidelines among Jordanian children and adolescents [version 4; peer review: 1 approved, 3 approved with reservations] - Islam K. Al-Shami; Buthaina Alkhatib; Huda Al Hourani; Ayoub Al-Jawaldeh (F1000Research)
Background Early-life food consumption patterns may affect children’s health by increasing susceptibility to developing non-communicable chronic diseases (NCDs) in adulthood. Aims To evaluate Jordanian children and adolescents’ energy and macronutrient intake and how closely they adhere to dietary recommendations. Methods This cross-sectional study used data from Jordan’s Population-based Food Consumption Survey, a household population-based study conducted in Jordan between 2021 and 2022 (561 children and adolescents 8-19 years). Dietary intake was assessed using the two non-consecutive 24-hour dietary recall methods (24-h DR). The estimated food group and nutrient intakes were compared to nutritional recommendations, including MyPlate dietary guidelines. Results The prevalence of overweight/obese individuals based on body mass index (BMI) was 44%, and the average waist-to-height ratio (WHtR) was 24.7%. Compared to MyPlate dietary guidelines, children and adolescents had a higher added sugar intake (57g/day). Also, consuming vegetables, fruits, and dairy fell short of MyPlate dietary guidelines. The total discretionary calorie intake in children and adolescents was approximately one-third of the total energy intake. Conclusion The food consumption of Jordanian children and adolescents includes high intakes of discretionary calories, with a low intake of fruits, vegetables, and dairy products. The prevalence of overweight/obesity was elevated compared to international norms.